The Past, Present and Future of a Hungarian Company - Baksi, Zsolt (International Journal of Engineering and Management Sciences, 2018)
The new strategy for small and medium-sized enterprises focuses on growth, the three pillars of which are the development of a knowledge-based and innovation-based economy, a resource efficient, greener and more competitive economy, and high employment and social and territorial cohesion. Based on the plans and forecasts, in the 2021-2028 cycle, however, it is not as much as today, but it is possible to calculate development resources closely linked to economic development in the form of non-refundable subsidies in many forms. In my present study, I wish to outline the life span of a Debrecen company, NEXT Broker Consulting Ltd. and its potential development prospects in the post-2020 cycle, which may be important because it deals with tender writing, so it can show a serious impression on the previous or current the direction and situation of the use of development resources, thus indirectly the realization of the goals of Hungarian economic policy.